A mediação das mulheres na constituição das redes informais de comunicação - Ribeiro, Neusa Maria Bongiovanni (Universidade do Vale do Rio do Sinos, 2007)
The thesis The mediation of the women in the constitution of the informal nets of communica-tion is on the idea of communication between women, through their speeches expressed and not expressed, and organized in the perspective of the groups where they are inserted. For that, at the group of workers of the Cooperative of Workers in the Footwear, of Boa Saúde quarter and Jardim Liberato, of Novo Hamburgo and the group of workers of the Restinga quarter had been observed two groups of women -, of Porto Alegre. The relations of commu-nication carried through by the women of the two groups are elements that, exactly crossed for the communication processes, present today in their life, generate a process throughout their life histories, witch pertains only to their reality, without being represented for the me-dias, in their daily knowledge. Estimating that the attitudes and procedures adopted for the women normally are of contribution for the development of other processes of advance of those groups, also in t
Keywords: comunicação comunitária; comunicação social; cooperativa; mídia; mulher; organização social; participação social; rede informal; trabalho; comunicação de massa; communication processes; communitarian communication; women; informal nets of communication; Ciências Sociais Aplicadas